2004
DOI: 10.1044/1092-4388(2004/094)
|View full text |Cite
|
Sign up to set email alerts
|

Phonologic Processing in Adults Who Stutter

Abstract: Event-related brain potentials (ERPs), judgment accuracy, and reaction times (RTs) were obtained for 11 adults who stutter and 11 normally fluent speakers as they performed a rhyme judgment task of visually presented word pairs. Half of the word pairs (i.e., prime and target) were phonologically and orthographically congruent across words. That is, the words looked orthographically similar and rhymed (e.g., thrown, own) or did not look similar and did not rhyme (e.g., cake, own). The phonologic and orthographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 51 publications
6
34
1
Order By: Relevance
“…More importantly, it is consistent with previous findings in other languages in which stutterers have 6 Carlos J. Álvarez et al been shown to take longer to read words and sentences than persons without stuttering (Postma, Kolk, & Povel, 1990;Weber-Fox, Spencer, Spruill, & Smith, 2004). For example, in the study by Postma et al (1990), longer timeframes were found in different kinds of linguistic material production between stutterers and nonstutterers not only in the sub-vocalization and overt articulation conditions, but also in silent reading.…”
Section: Discussionsupporting
confidence: 91%
“…More importantly, it is consistent with previous findings in other languages in which stutterers have 6 Carlos J. Álvarez et al been shown to take longer to read words and sentences than persons without stuttering (Postma, Kolk, & Povel, 1990;Weber-Fox, Spencer, Spruill, & Smith, 2004). For example, in the study by Postma et al (1990), longer timeframes were found in different kinds of linguistic material production between stutterers and nonstutterers not only in the sub-vocalization and overt articulation conditions, but also in silent reading.…”
Section: Discussionsupporting
confidence: 91%
“…In terms of speech planning difficulties, a considerable amount of data implicate weaknesses in phonological encoding early in life as a key area of compromise (e.g., [7-9], for an opposing viewpoint, see [10, 11]), particularly for children whose stuttering persists into adulthood (e.g., [12-15]). These data are further supported by studies which indicate that many adults who stutter (AWS) perform more poorly than adults who do not stutter (AWNS) when completing experimental tasks that rely on efficient phonological processing (e.g., nonword repetition [16-18]; silent error monitoring [19]; phoneme elision [16, 17]; word jumble tasks [20]; silent rhyme judgment [21, 22]; silent phoneme monitoring [23-25]). Although differences in the phonological abilities of AWS are not unequivocal (cf.…”
Section: Introductionsupporting
confidence: 53%
“…For example, Weber-Fox (2001) reported that AWS versus TFA evidenced attenuated ERP effects to both grammatical and semantic word classes during a sentence reading task. In a later study, Weber-Fox et al (2004) reported that ERP correlates of phonological processing, elicited during a rhyme judgment task for pairs of printed words, were similar in AWS and TFA. The former findings were taken to indicate that neural functions related to lexical retrieval may be altered in AWS, while the latter findings were taken to indicate that adulthood stuttering may not stem from phonological processing deficits.…”
Section: Introductionmentioning
confidence: 92%